Zooplankton community in Thi Nai lagoon in the period of 2001–2020 - Nguyen, Vinh Tam; Hai, Doan Nhu (Vietnam Journal of Marine Science and Technology, 2021)
This paper presents the results of the surveys on zooplankton in Thi Nai lagoon from 2001 to 2020. There were 179 species found in the lagoon, among which Copepod was the dominant group with 97 species (50.78% of total species), followed by Cladocera with 20 species (10.36%), Hydrozoa with 18 species (9.33%), Tunicata with 11 species (5.7%) and Siphonophora with 10 species (5.18%). Based on Bray-Curtis similarity analysis of zooplankton community and the station position, the sampling stations in the lagoon were grouped into three areas: The upper lagoon (UP), the middle (MI), and the mouth of the lagoon (MO). Among the surveyed years, there was a slight variation in the species number, while the density decreased by time and was especially low in 2020. Zooplankton density was much lower in the rainy season compared to that in the dry season, while the species number was less varied. Analysis of the differences between the areas in the lagoon demonstrated a clear distribution pattern of zooplankton with a decreasing density and an increasing number of species from upper lagoon to the mouth of the lagoon. Zooplankton diversity was less affected by time and only the Pielou index in the MI area between 2004 and 2009 was significantly different. Analysis of the various indices between seasons showed that the MO area was less volatile than the two other regions. The multi-dimensional scaling analysis demonstrated that zooplankton community was less variable by regions (50% similarity) compared to by the years (only 30% of similarity), except in 2009 and 2020 when differences among the areas were significant. Seasonal community change between the dry and rainy seasons was 30%.